Старый знакомый гликлазид: место в современной сахароснижающей терапии - Корпачева-Зиныч, О.В.; Гурина, Н.М.; Кушнарева, Н.Н. (Ендокринологія | Endokrynologia, 2014)
Старый знакомый гликлазид: место в современной сахароснижающей терапии